High frequency AC characteristics of 132kV power cable - Chakrabarty C.K.; Avinash A.R.; Ahmad Basri A.G. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cables; Capacitance; Capacitors; Defects; Electric fields; Insulation; Phase shift; Phase shifters; Dissipation factors; High frequency HF; HVAC; Tangent delta; XLPE; Electric insulation